Faktor-Faktor yang Mempengaruhi Kejadian Hiperemesis Gravidarum pada Ibu Hamil di Puskesmas Pagar Merbau Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2023 - Nurasiah Nurasiah; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Agustina Susilawati Tumangger (NAJ Nursing Applied Journal, 2024)
Hyperemesis gravidarum is a condition of excessive nausea and vomiting in pregnant women that is worse than morning sickness, the cause is unknown. Psychological factors can worsen this condition, causing dehydration, weight loss, electrolyte imbalance, and complications such as liver damage and retinal hemorrhage due to increased blood pressure during vomiting. Treatment is done by administering fluids, glucose, electrolytes, and vitamins through an IV. This study aims to analyze the factors that influence the incidence of hyperemesis gravidarum at the Pagar Merbau Health Center, Deli Serdang, in 2023. This study uses a descriptive correlational method with a cross-sectional design to analyze the relationship between independent and dependent variables simultaneously. Data were collected retrospectively from 36 respondents using a purposive sampling technique. The research instruments were questionnaires and observation sheets, while data analysis was carried out using the chi-square statistical test which showed a p value = 0.021. There is a significant relationship between age, knowledge, parity, and multiple pregnancies with the incidence of hyperemesis gravidarum in pregnant women at the Pagar Merbau Health Center, Deli Serdang.